Proximate components, minerals, amino acids and some anti-nutrients in processed false yam seed meals: Potential benefits for poultry nutrition - Mohammed Alhassan; Herbert Kwabla Dei; Addah Wesseh; Regina Roessler; Eva Schlecht (Scientific African, 2019)
This study investigated the effect of sequential processing techniques (water treatment, chemical treatment and blanching) of false yam seed meal (FYSM) on its proximate composition, mineral and amino acid concentrations and anti-nutritional compounds. Matured false yam (Icacina oliviformis) fruits were harvested and seeds extracted. Five different FYSM samples were prepared. One sample was prepared by crushing fresh false yam seed and sun-drying (Un_T). Four other samples were crushed, each soaked in water (1:2; w/v) for 12 days with water replaced every 3 days. Afterwards, each sample was re-soaked in 1 M concentration of urea (Urea_T), sodium chloride (NaCl_T), sodium hydroxide (NaOH_T) and potassium hydroxide (KOH_T), respectively, for 24 h, washed, blanched and sun-dried to a moisture content of 12%. Sample analysis revealed high dry matter [DM; 89% (NaOH_T) – 93% (KOH_T)] and carbohydrate [71.4% (Un_T) – 83.9% (NaCl_T)] content but a reduction of crude protein from 13.2% (Un_T) to 2.2% (KOH_T). Mineral analysis showed a reduction in Ca from 280 (Un_T) to 24 mg/kg DM (NaCl_T) and in Mg from 52.8 (Un_T) to 13.29 mg/kg DM (Urea_T) but an improvement in K from 110.6 (Un_T) to 368.8 mg/kg DM (KOH_T), in Na [from 558 (Un_T) to 989 mg/kg DM (NaCl_T)] and total P [from 0.31 (Un_T) to 2.37 mg/kg DM (Urea_T)]. Amino acid composition of FYSM was negatively affected by all treatments. Concentrations of anti-nutritional factors, namely total terpenes and saponins, were reduced by 82% (KOH_T) to 92% (Urea_T) and by 68% (KOH_T) to 77% (NaCl_T), respectively. In vitro gas production per 380 mg of sample was similar across treatments. Reducing anti-nutritional factors by sequential use of simple processing methods with easily available chemicals offers the potential to use FYSM in livestock diets. Yet, as some nutrient concentrations are negatively affected, in vivo trials are needed to determine the nutritional value of treated FYSM. Keywords: Anti-nutritional factors, Chemical processing, Icacina oliviformis, Proximate composition